Feasible low bone density condition for assessing bioactivity in ex-in vivo and in vivo studies - William Phillip Pereira DA SILVA; Leonardo Alan DELANORA; Barbara Ribeiro RIOS; Stéfany BARBOSA; Maria Eloise de Sá SIMON; Cortino SUKOTJO; Leonardo P FAVERANI (University of São Paulo, 2023)
Abstract Objective To choose a critical animal model for assessments of bone repair with implant installation by comparing senile rats (SENIL) to young ovariectomized rats (OXV). Methodology For the ex-in vivo study, the femurs were precursors for bone marrow mesenchymal stem cells. Cellular responses were performed, including cell viability, gene expression of osteoblastic markers, bone sialoprotein immunolocalization, alkaline phosphatase activity, and mineralized matrix formation. For the in vivo study, the animals received implants in the region of the bilateral tibial metaphysis for histometric, microtomography, reverse torque, and confocal microscopy. Results Cell viability showed that the SENIL group had lower growth than OVX. Gene expression showed more critical responses for the SENIL group (p<0.05). The alkaline phosphatase activity obtained a lower expression in the SENIL group, as for the mineralization nodules (p<0.05). The in vivo histological parameters and biomechanical analysis showed lower data for the SENIL group. The confocal microscopy indicated the presence of a fragile bone in the SENIL group. The microtomography was similar between the groups. The histometry of the SENIL group showed the lowest values (p<0.05). Conclusion In experimental studies with assessments of bone repair using implant installation, the senile model promotes the most critical bone condition, allowing a better investigation of the properties of biomaterials and topographic changes.